2020
DOI: 10.3390/plants9070814
|View full text |Cite
|
Sign up to set email alerts
|

Late Embryogenesis Abundant Protein–Client Protein Interactions

Abstract: The intrinsically disordered proteins belonging to the LATE EMBRYOGENESIS ABUNDANT protein (LEAP) family have been ascribed a protective function over an array of intracellular components. We focus on how LEAPs may protect a stress-susceptible proteome. These examples include instances of LEAPs providing a shield molecule function, possibly by instigating liquid-liquid phase separations. Some LEAPs bind directly to their client proteins, exerting a holdase-type chaperonin function. Finally, instances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 167 publications
(230 reference statements)
0
33
0
Order By: Relevance
“…Dehydrins are considered as molecular protectors by interacting with protective target proteins against different abiotic stress (Dirk et al., 2020). Based on a screen to identify potential interaction proteins of MsDHN1, two AQPs (MsPIP2;1 and MsTIP1;1) were proven to interact with MsDHN1 using Y2H, BiFC and Co‐IP (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrins are considered as molecular protectors by interacting with protective target proteins against different abiotic stress (Dirk et al., 2020). Based on a screen to identify potential interaction proteins of MsDHN1, two AQPs (MsPIP2;1 and MsTIP1;1) were proven to interact with MsDHN1 using Y2H, BiFC and Co‐IP (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…dehydrated cells (30). However, previous bioinformatics analysis of AfrLEA6 also identified sequence features associated with proteins known to undergo LLPS to form membraneless organelles (MLOs), which warranted a more thorough evaluation on the possible role of LLPS in animal anhydrobiosis (14,27,31,32).…”
Section: Significancementioning
confidence: 99%
“…In vitro evidence suggested that LEA proteins ensure enzyme activity, act as a molecular shield preventing protein aggregation and as chaperone, stabilize and associate with membranes, sequester ions and reactive oxygenic species, prevent cellular water loss by acting as hydration buffer, and stabilize sugar glasses by increasing the glass transition temperature [ 4 , 5 , 12 , 14 , 17 ]. In addition, the IDP-structure of LEA proteins might contribute to a phenomenon named liquid-liquid phase separation (LLPS), a process which gives rise to proteinaceous membrane-less organelles [ 18 ]. Nevertheless, not all IDPs undergo LLPS and intrinsically disordered regions (IDRs) are not necessarily required for LLPS.…”
Section: Introductionmentioning
confidence: 99%
“…LEA proteins are able to interact with each other or other proteins. Direct LEA-target protein interactions have been shown among the LEA_2, dehydrin, LEA_4, and the SMP protein families [ 18 ]. As an example, dehydrins AtCOR47, AtERD10, and AtRAB18 bound to the aquaporin AtPIP2B and a homodimeric interaction of RAB18 complexes was revealed as well as a heterodimeric association between AtRAB18 acidic dehydrins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation